Penerapan Konsep Desain Norman Foster Pada Bangunan Convention and Exhibition Center di Kota Medan - Irwan Telaumbanua; Ina Triesna Budiani (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2023)
Medan City is the 3rd largest city in Indonesia where Medan City is also a city of industry, business and trade which is very influential in Indonesia so that it has enormous opportunities in the tourism industry sector in the field of MICE (Meeting, Incentive, Convention and Exhibition), so infrastructure is needed in the form of a convention and exhibition center building which has complete facilities so that it can support every activity related to MICE, this is intended to improve the economy of Medan City in the tourism industry sector and is supported by the election of Indonesia as the host of the G20 Presidency which allows investors from other countries to others to carry out business activities in the city of Medan. The design of this convention and exhibition center applies the Norman Foster design concept, where the concept of sustainable architectural design, engineering, urbanism, and industrial design has special design characteristics, one of which is an approach to high-tech design characters, where the use of iron/steel and glass materials which will be found in many of these buildings so as to give a new feel to the area.